Social Capital Construction and Governance in Central Asia : Communities and NGOs in post-Soviet Uzbekistan - Dadabaev, Timur; Ismailov, Murod; Tsujinaka, Yutaka (Politics and History in Central Asia, 2017)
This cutting edge collection focuses on the nature of civil society and its role in facilitating governance in Central Asia, considering local implications related to the concept of social capital and civil society in the Uzbek context. It discusses the complexity of the notion of social capital in post-Soviet Uzbekistan, detailing the challenges and pressures facing the Uzbek people. Challenging prevailing views on post-Soviet political transitions, the book demonstrates that successful transition to democracy and rule of law cannot be accomplished unless the concerns, fears, frustrations and local understandings of the desired political system are heard, registered and carefully interpreted. Offering a comparative study of civil society and social capital in Asia, this collection is a key read not only for scholars and students in civil governance and post-soviet transitions, but also aid agencies, foreign governments, and international organisations working with civil society groups.- Resumé vydavatel